2016
DOI: 10.4103/0301-5742.175709
|View full text |Cite
|
Sign up to set email alerts
|

Cone-beam computed tomography evaluation of dental, skeletal, and alveolar bone changes associated with bonded rapid maxillary expansion

Abstract: Aims and Objectives: To evaluate skeletal changes in maxilla and its surrounding structures, changes in the maxillary dentition and maxillary alveolar bone changes produced by bonded rapid maxillary expansion (RME) using cone-beam computed tomography (CBCT). Materials and Methods: The sample consisted of 10 patients (6 males and 4 females) with age range 12 to 15 years treated with bonded RME. CBCT scans were performed at T1 (pretreatment) and at T2 (immediately after expansion) to evaluate the dental, skeleta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Finally, a sensitivity analysis was performed for the main outcome (maxillary basal bone width) after the active expansion phase (T 1 -T 0 ) while excluding the trial by Dogra et al, 15 which showed a higher risk of bias. The sensitivity analysis showed similar results as the corresponding complete analysis, thus confirming the results of the overall meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, a sensitivity analysis was performed for the main outcome (maxillary basal bone width) after the active expansion phase (T 1 -T 0 ) while excluding the trial by Dogra et al, 15 which showed a higher risk of bias. The sensitivity analysis showed similar results as the corresponding complete analysis, thus confirming the results of the overall meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Of the remaining potentially appropriate trials, 18 articles were identified as eligible to be included in qualitative and quantitative final synthesis. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] The compete flow diagram of included studies designed according to the PRISMA guideline is provided in Figure 1.…”
Section: Selection Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation